"There is no surer way to drive off Covid than to sing it". Intersected views on music in France (2020-2022) (Revista Argentina de Musicología, 2022)
Since March 2020, the Covid-19 pandemic has had a huge impact on artistic practices in France, in particular on the performing arts and on the working conditions of professional musicians. Our research analyzes these changes in relation to the systems of coercion, the resources generated by this crisis and the issues that are at stake in these transformations. It proposes a first typology that allows us to give meaning to the musical practices surveyed. It identifies the main significant trends and proposes realistic projections that allow us to foresee the musical world of “the day after”.
Keywords: pandemic; Covid-19; musical practices; France